2020
DOI: 10.3390/ijerph17249269
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Correlates of Cycling to School among 12- to 15-Year Olds in Southern Germany

Abstract: Depending on the region and urbanization level, the rate of cycling to school in Germany varies largely. The influence of distance from home to school, educational level, the school’s region, and parents’ socio-demographic characteristics on cycling to secondary school in Germany is unclear. Therefore, this study analyzed students’ and parents’ socio-demographic correlates of cycling to school, including separate analyses by gender, among 12- to 15-year-olds attending different (sub)urban schools in Southern G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
(48 reference statements)
2
11
0
Order By: Relevance
“…As none of these mentioned needs stood out as particularly (un)important and/or (un)feasible, we treated all of them as equally relevant. In this study, almost all students owned a bicycle (girls: 87.8%, boys: 100%) and all were able to cycle ( 5 ). When examining the habits of the students in cycling to school, we found that approximately two-thirds of students stated to sometimes cycle to school (girls: 44.4%, boys: 72.9%), of whom approximately one-third cycled to school daily (girls: 31.6%, boys: 37.3%).…”
Section: Methods and Analysismentioning
confidence: 68%
See 4 more Smart Citations
“…As none of these mentioned needs stood out as particularly (un)important and/or (un)feasible, we treated all of them as equally relevant. In this study, almost all students owned a bicycle (girls: 87.8%, boys: 100%) and all were able to cycle ( 5 ). When examining the habits of the students in cycling to school, we found that approximately two-thirds of students stated to sometimes cycle to school (girls: 44.4%, boys: 72.9%), of whom approximately one-third cycled to school daily (girls: 31.6%, boys: 37.3%).…”
Section: Methods and Analysismentioning
confidence: 68%
“… Logic model of the problem: Factors that influence cycling to school based on concept mapping ( 5 , 17 ). …”
Section: Methods and Analysismentioning
confidence: 99%
See 3 more Smart Citations